MILITARY CAPABILITIES AND THE STRATEGIC PLANNING CONUNDRUM - João CORREIA (Security and Defence Quarterly, 2019)
This paper aims to question the military capability concept, as a core element of the strategic military planning process, in order to determine its validity or need for expansion. Thus, based on a deductive approach and qualitative research, we argue that the strategic planning process is a conundrum so dependent on capabilities that it is necessary to analyse this concept per se and, if necessary, expand it on a time and threat basis. Otherwise, the more ambiguous the concept, the more subjective the planning process output and, consequently, the greater likelihood of the Armed Forces not being prepared to face the wide range of future challenges. It concludes by suggesting that the military capability concept should be expanded and more integrated and the strategic defence planning process adapted accordingly.